P04-S Dose-dependent synchronization of ongoing alpha oscillation by repetitive transcranial magnetic stimulation. Issue 7 (July 2019) - Zmeykina, Elina; Turi, Zsolt; Paulus, Walter
Abstract : Repetitive transcranial magnetic stimulation (rTMS) is shown to modulate ongoing neural activity by means of inducing an oscillating electric field (E-field) in the cortical regions. Traditionally, rTMS induces an intracranial peak E-field in the range of 90–110 V/m. However, in vitro experiments show that a 1–5 V/m E-field is enough to entrain ongoing rhyth. Therefore, we hypothesized that inducing E-fields magnitudes less than 50 V/m is enough to entrain ongoing parietal alpha oscillations. We tested the hypothesis by enrolling sixteen healthy participants in a single-blind, repeated measure study. First, we estimated the magnitudes of E-fields by using MR-derived realistic head models. Participants were stimulated with three intensities corresponding to 20 (LOW), 35 (MED) and 50 (HIGH) V/m E-fields. The bursts of 20 TMS pulses were applied at individual alpha frequency. The effect was controlled by arrhythmic stimulation that consisted of twenty pulses at random intra-burst frequencies. rTMS induced effect was studied during and after rTMS by electrophysiological changes of parietal alpha. We found that phase synchronization of an ongoing activity with external pulses was increased during rhythmic rTMS but not for arrhythmic rTThe amount of synchronization expressed in phase locking values was progressively larger for increasing intensity in a dose-dependent manner. After effects of rTMS were present for LOW and HIGH stimulation intensities. Rhythmic rTMS increased while arrhythmic rTMS decreased the power of parietal alpha. Overall, our study demonstrated that rTMS at intensities about two times lower than those traditionally used could successfully modulate the parietal alpha rhythm in resting state.